A novel surgical approach for treatment of sigmoid gallstone ileus. (6th July 2015) - Cargill, Abbey; Farkas, Nicholas; Black, John; West, Nicholas
Abstract : We report a rare case of large bowel obstruction secondary to a gallstone impacted within the sigmoid colon, in the presence of sigmoid diverticular disease. An 89-year-old woman presented with an 8-day history of increasing abdominal distension, pain and associated nausea. Abdominal X-ray demonstrated large bowel dilation. CT scan revealed a fistula between an inflamed gallbladder and the hepatic flexure of the colon, with a large gallstone in the sigmoid colon. Proximal dilated large bowel was evident to the caecum. Flexible sigmoidoscopy was performed as the least invasive potential treatment method with a view to basket retrieval or fragmentation of the stone. Owing to poor views and risk of diverticular perforation, the procedure was abandoned, hence laparotomy was performed. Antegrade manipulation and per-rectal evacuation were attempted but failed due to a thickened, angulated sigmoid colon. Retrograde milking of the stone to the caecum and retrieval via modified appendicectomy was successful.